2006
DOI: 10.1124/jpet.105.100354
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cannabinoid Type-1 Receptor Mediates the Anticonvulsant Properties of Cannabinoids in the Hippocampal Neuronal Culture Models of Acquired Epilepsy and Status Epilepticus

Abstract: Cannabinoids have been shown to have anticonvulsant properties, but no studies have evaluated the effects of cannabinoids in the hippocampal neuronal culture models of acquired epilepsy (AE) and status epilepticus (SE). This study investigated the anticonvulsant properties of the cannabinoid receptor agonist R(ϩ)- [2,3-dihydro-5-methyl-3-[(morpholinyl) (WIN 55, in primary hippocampal neuronal culture models of both AE and SE. WIN 55,212-2 produced dose-dependent anticonvulsant effects against both spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 37 publications
5
93
1
1
Order By: Relevance
“…Previous in vitro and in vivo studies have shown that exogenously applied CB receptor agonists, such as D 9 THC and WIN 55, 212-2 are antiepileptic in a number of animal seizure models. This includes in vivo models of maximal electroshock in mice (Wallace et al, 2001) and the pilocarpine model in rats (Wallace et al, 2003), and in vitro, in hippocampal neuronal culture models of acquired epilepsy and status epilepticus (Blair et al, 2006). Moreover, endocannabinoids such as AEA and 2-AG have been shown to exhibit neuroprotective effects (Marsicano et al, 2003) and antiepileptic effects when applied exogenously (Wallace et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro and in vivo studies have shown that exogenously applied CB receptor agonists, such as D 9 THC and WIN 55, 212-2 are antiepileptic in a number of animal seizure models. This includes in vivo models of maximal electroshock in mice (Wallace et al, 2001) and the pilocarpine model in rats (Wallace et al, 2003), and in vitro, in hippocampal neuronal culture models of acquired epilepsy and status epilepticus (Blair et al, 2006). Moreover, endocannabinoids such as AEA and 2-AG have been shown to exhibit neuroprotective effects (Marsicano et al, 2003) and antiepileptic effects when applied exogenously (Wallace et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoid compounds have been reported to exhibit both antiepileptic (Blair et al, 2006;Wallace et al, 2001; and neuroprotective properties (Marsicano et al, 2003) via cannabinoid receptors. The endogenous cannabinoid (endocannabinoid) system is integral in controlling neuronal excitability and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were conducted on primary mixed hippocampal neuronal cultures prepared as described previously with slight modifications (Blair et al, 2006;Deshpande et al, 2007b;Sombati and DeLorenzo, 1995). In brief, hippocampal cells were obtained from 2-day postnatal Sprague-Dawley rats (Harlan, Frederick, MD) and plated at a density of 1 × 10 5 cells/cm 2 onto 35-mm Falcon cell culture dishes (Becton Dickinson and Co., Franklin Lakes, NJ) previously coated with poly-L-lysine (0.05 mg/ml).…”
Section: Hippocampal Neuronal Culturementioning
confidence: 99%
“…This has possible implications in pathological manifestations of inhibition and excitation imbalance such as epilepsy (Blair, 2006). Interestingly, CBs have been found to exert both convulsant and anticonvulsant effects (Monory and Lutz, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an upregulation of CB 1 receptors on GABAergic terminals but not on glutamatergic terminals has been observed due to febrile seizures, suggesting a pathological enhancement of DSI (Chen et al, 2007). Also, it has been hypothesised that suppression of excitation is the mode of action of the anti-convulsant effects of CBs (Blair, 2006;Hajos and Freund, 2002). This hypothesis has been supported in a study by Monory et al (Monory et al, 2006) where deletion of CB 1 receptors from glutamatergic terminals was shown to be pro-convulsant whereas the deletion of CB 1 receptors from GABAergic cells did not change seizure behaviour.…”
Section: Discussionmentioning
confidence: 99%